Artropatia de Charcot aguda: abordagem cirúrgica - Batista, Fábio; Pinzur, Michael S. (Tobillo y Pie, 2014)
Objective: The Charcot osteoarthropathy is a progressive, disfiguring, and debilitating condition characterized by joint subluxation and dislocation, fracture, and extensive osseous destruction of the foot architecture due to severe peripheral neuropathy. This progressive disease process is precipitated with repetitive trauma that goes unrecognized because of a loss of sensation and reactive hyperemia. Methods: We have been operated 20 Acute Charcot arthropathy at the last 3 years, with Achiles lengtheting, exostectomy, joint realignment, debridement, static external fixation (one stage approach) and internal fixation with cannulated screws (staged approach) immediately to external fixation removal, to prevent future instability-collapse and ulcer recurrence, in active patient with no evidence of bone infection. Results: Follow-up was performed through a multidisciplinary team to maintain metabolic and glycemic control, provide education strategies to prevent recurrence of lesions, and also physical therapy for adequate function and protection. During the study, none of the patients presented with deep infection or non plantigrade or unstable foot. Two patients presented superficial infection and underwent managed appropriately with antibiotics, skin care and local protection. Conclusion: Acute correction of Charcot joint using static external fixation alone minimizes the need for extensive surgical exposure and may provide a means of reducing deformities while maintaining the reduction during consolidation.